Pemberdayaan Generasi Milenial Nasyiatul ‘Aisyiyah Seyegan Menuju Terwujudnya Remaja Sehat Berkemajuan - Handayani, Nia; Purnamasari, Vita; Azizah, Aisyah Nur (Lembaga Penelitian dan Pengabdian Masyarakat (LPPM) STIKES Cendekia Utama Kudus, 2024)
Nasyiatul 'Aisyiyah (NA) as part of the autonomous Muhammadiyah organization also contributes to realizing Muhammadiyah's goals in the women's movement segment. NA's contribution to realizing Muhammadiyah's goals for young women in particular. Teenagers are an age group that is the focus of attention for human resource development. Important steps need to be taken because adolescent groups face greater risks and are more vulnerable in the social environment. The millennial era is a period influenced by the sophistication of science and technology which has an influence on attitudes and behavior. The environment undergoes major changes during adolescence and often plays a risky role in adolescent health status. The health status of today's adolescents will determine the picture of the health status of the adult population in the future. The majority of the millennial generation uses technology to make their lives easier, such as searching for information via the internet. To move towards a progressive millennial generation, the hope is that they can make good use of technological developments in developing information in the health sector